Re-Discovery of Giardiavirus: Genomic and Functional Analysis of Viruses from Giardia duodenalis Isolates - Gianluca Marucci; Ilaria Zullino; Lucia Bertuccini; Serena Camerini; Serena Cecchetti; Agostina Pietrantoni; Marialuisa Casella; Paolo Vatta; Alex D. Greenwood; Annarita Fiorillo; Marco Lalle (Biomedicines, 2021)
Giardiasis, caused by the protozoan parasite Giardia duodenalis, is an intestinal diarrheal disease affecting almost one billion people worldwide. A small endosymbiotic dsRNA viruses, G. lamblia virus (GLV), genus Giardiavirus, family Totiviridae, might inhabit human and animal isolates of G. duodenalis. Three GLV genomes have been sequenced so far, and only one was intensively studied; moreover, a positive correlation between GLV and parasite virulence is yet to be proved. To understand the biological significance of GLV infection in Giardia, the characterization of several GLV strains from naturally infected G. duodenalis isolates is necessary. Here we report high-throughput sequencing of four GLVs strains, from Giardia isolates of human and animal origin. We also report on a new, unclassified viral sequence (designed GdRV-2), unrelated to Giardiavirus, encoding and expressing for a single large protein with an RdRp domain homologous to Totiviridae and Botybirnaviridae. The result of our sequencing and proteomic analyses challenge the current knowledge on GLV and strongly suggest that viral capsid protein translation unusually starts with a proline and that translation of the RNA-dependent RNA polymerase (RdRp) occurs via a +1/−2 ribosomal frameshift mechanism. Nucleotide polymorphism, confirmed by mass-spectrometry analysis, was also observed among and between GLV strains. Phylogenetic analysis indicated the occurrence of at least two GLV subtypes which display different phenotypes and transmissibility in experimental infections of a GLV naïve Giardia isolate.